Environmental responsibility and pro-environmental behavior: Biology undergraduate students’ profile - Diana Vivanti Sigit; Eka Putri Azrai; Erna Heryanti; Kasih Anggraeni; Ilmi Zajuli Ichsan; Rahmat Fadrikal (University of Muhammadiyah Malang, 2019)
Environmental responsibility is a crucial aspect which determines the environmental solving problems in term of enhancing the pro-environmental behavior. This study aimed to examine the relation between the environmental responsibility and pro-environmental behavior of the undergraduate students. The sample of this descriptive correlational study was 106 students of biology education department which was taken randomly. This study showed that the undergraduate students were in high criteria of environment responsibility (ER). This was represented by feeling guilty which was the highest percentage and followed by responsibility feeling and responsibility judgment respectively. In addition, the undergraduate students were in positive pro-environmental behavior (PEB). The regression model was y = 23.876 + 0.623x; while ER contributed as high as 22.1% to the undergraduate student’s PEB. This implied that to improve the undergraduate student’s PEB is by strengthening their ER.